A NAC transcription factor and its interaction protein hinder abscisic acid biosynthesis by synergistically repressing NCED5 in Citrus reticulata. (31st May 2020) - Zhu, Feng; Luo, Tao; Liu, Chaoyang; Wang, Yang; Zheng, Li; Xiao, Xue; Zhang, Mingfei; Yang, Hongbin; Yang, Wei; Xu, Rangwei; Zeng, Yunliu; Ye, Junli; et al.
Abstract : A novel NAC transcription factor, CrNAC036, can interact with CrMYB68 to synergistically regulate the ripening process of citrus fruit by down-regulating the expression of 9-cis-epoxycarotenoid dioxygenase 5 . Abstract: Although abscisic acid (ABA) is a vital regulator of fruit ripening and several transcription factors have been reported to regulate ABA biosynthesis, reports of the effect of ABA on citrus ripening and the regulation of its biosynthesis by a multiple-transcription-factor complex are scarce. In the present study, a systematic metabolic, cytological, and transcriptome analysis of an ABA-deficient mutant (MT) of Citrus reticulata cv. Suavissima confirmed the positive effect of ABA on the citrus ripening process. The analysis of transcriptome profiles indicated that CrNAC036 played an important role in the ABA deficiency of the mutant, most likely due to an effect on the expression of 9-cis-epoxycarotenoid dioxygenase 5 ( CrNCED5 ). Electrophoretic mobility shift assays and dual luciferase assays demonstrated that CrNAC036 can directly bind and negatively regulate CrNCED5 expression. Furthermore, yeast two-hybrid, bimolecular fluorescence complementation, and dual luciferase assays demonstrated that CrNAC036 interacted with CrMYB68, also down-regulating the expression of CrNCED5 . Taken together, our results suggest that CrNAC036 and CrMYB68 synergistically inhibit ABA biosynthesis in citrus fruit by regulating the expression of CrNCED5 .